2007
DOI: 10.1111/j.1365-2036.2007.03542.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: multispecies probiotic supplementation alleviates the symptoms of irritable bowel syndrome and stabilizes intestinal microbiota

Abstract: SUMMARY BackgroundIrritable bowel syndrome is the most common diagnosis in gastroenterology. Trials suggest certain probiotics to be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
243
1
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(265 citation statements)
references
References 40 publications
(75 reference statements)
10
243
1
10
Order By: Relevance
“…A recent Cochrane review of dietary intervention in functional bowel disorders in children has found insufficient evidence to support its use (64) . It should be noted that L. GG is a composite strain in one of the probiotic cocktails that have showed benefit in two larger trials (60,65) . (57) 12 L. plantarum 299V; 10 7 4 Failed to show reduction in GSS over placebo Niedzielin et al (55) 40 L. plantarum 299V; 10 7 4 PEP defined as resolution of pain; 100 % v. 55% (P < 0 .…”
Section: Lactobacillus Ggmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Cochrane review of dietary intervention in functional bowel disorders in children has found insufficient evidence to support its use (64) . It should be noted that L. GG is a composite strain in one of the probiotic cocktails that have showed benefit in two larger trials (60,65) . (57) 12 L. plantarum 299V; 10 7 4 Failed to show reduction in GSS over placebo Niedzielin et al (55) 40 L. plantarum 299V; 10 7 4 PEP defined as resolution of pain; 100 % v. 55% (P < 0 .…”
Section: Lactobacillus Ggmentioning
confidence: 99%
“…These findings were confirmed by a follow-up study of eighty-six patients, with a difference in reduction in GSS of eleven points (P< 0 . 01) (60) . However, marked differences in baseline severity scores were found between treatment groups and controls, with the treatment group having greater symptom severity and therefore more likely to improve.…”
Section: Vsl#3mentioning
confidence: 99%
“…Two studies were performed by the same research group with the same preparation. 74,76 The use of Streptococcus thermophilus and Lactobacillus bulgaricus as starting cultures for yoghurt production is occasionally noted; in the remaining cases it remains unclear whether these strains were included. They were not regarded as probiotics until 2014, when the ISAPP consented that they are probiotics by definition.…”
Section: Bacterial Strain Combinationsmentioning
confidence: 99%
“…However, a limitation of this study was the small number of patients with samples who could be included in the analysis of gut microbiota (n = 20) [100].…”
Section: Other Multispecies Probioticsmentioning
confidence: 99%
“…However, further analyses are needed to definitively demonstrate this potential association between alterations in the gut microbiota and improvement in specific IBS symptoms. Kajander et al [100] reported that treatment with a multispecies probiotic stabilized the gut microbiota Kim et al R, DB, PBO-C Pts with IBS by self-report (Rome II criteria) LAB4 multistrain probiotic (Cultech Ltd., Port Talbot, UK)…”
Section: Other Multispecies Probioticsmentioning
confidence: 99%